Disorders of the statics of the body and the temporomandibular joint - Martyna Odzimek; Katarzyna Maj-Gnat (Kazimierz Wielki University, 2021)
INTRODUCTION The temporomandibular joint is a synovial, complex (hinge-sliding) joint that connects the temporal bone with the mandible by means of an articular disc. Temporomandibular joint dysfunctions most often concern several disease entities and include various symptoms and ailments. One of the first symptoms of the disease is pain that stems from a muscle or joint. In addition, we can observe: limitations in the mobility and range of movement of the jaw, problems with chewing food, crackles in the joint, pain in pressure and touch of the muscles, earaches and noise or changes in the appearance of the face (the so-called "square face"). Any deviation from the correct body posture is called a posture defect. OBJECTIVE The main aim of the study is to present the significant relationship between disturbed statics of the body and the temporomandibular joint, thanks to which we can explain the importance of proper planning of diagnostics as well as conducting dental and physiotherapeutic therapy. THE WEIGHT OF THE BODCIES The materials used to write the article include scientific works from 1992-2021. The data was collected using the PubMed search engine and manual filtering. 80 publications were qualified for the analysis. SUMMARY According to the analyzed literature, we believe that there is a relationship between disturbances in the body statics and the stomatognathic system. The complexity of the issue shows that it is important to conduct multi-directional and interdisciplinary therapy.